High-Density Genetic Map Construction and QTL Mapping of Leaf and Needling Traits in Ziziphus jujuba Mill - Wang, Zhongtang; Zhang, Zhong; Tang, Haixia; Zhang, Qiong; Zhou, Guangfang; Li, Xingang (Frontiers in Plant Science, 2019)
The Chinese jujube (Ziziphus jujuba Mill., 2n = 2 x = 24), one of the most popular fruit trees in Asia, is widely cultivated and utilized in China, where it is traditionally consumed as both fresh and dried food sources. A high-density genetic map can provide the necessary framework for quantitative trait loci (QTL) analyses, map-based gene cloning, and molecular breeding. In this study, we constructed a new high-density genetic linkage map via a genotyping-by-sequencing (GBS) approach. For the consensus linkage map, a total of 3792 markers spanning 2167.5 cM were mapped onto 12 linkage groups, with an average marker distance of 0.358cM. The genetic map anchored 301 Mb (85.7%) of scaffolds from the sequenced Z. jujuba ‘Junzao’ genome. Based on this genetic map, 30 potential QTLs were detected, including 27 for leaf traits and 3 for needling length. This high-density genetic map and the identified QTLs for relevant agronomic traits lay the groundwork for functional genetic mapping, map-based cloning and marker-assisted selection (MAS) in the jujube.